A Change in the Image of the Wolf (Canis lupus) in the Poles’ Public Awareness – the Demand for Environmental Education - Klimski, Marcin; Gadziński, Mikołaj (Studia Ecologiae et Bioethicae, 2025)
The public awareness of the grey wolf (Canis lupus) is shaped by various messages. Among these, undoubtedly the most influential are those related to repeated stereotypes, often based on unverified sources or even misinformation. As a consequence, it leads to numerous human-wolf conflicts. The aim of this article is to highlight the role of environmental education, conducted in its various forms, in changing the social perception of Canis lupus. The paradox observed in the public image of the wolf somewhat compels the implementation of effective environmental education with a view toward its protection. An analytical-synthetic method was applied in this paper, which enabled the formulation of conclusions from the collected research material. Among these are findings indicating that building a positive image of the predator should be based on reliable scientific data. Moreover, selecting appropriate educational methods and forms allows scientific data to be presented to all recipients of the educational process, from the youngest children to adults. Consequently, environmental education delivered in this way to various social groups shapes a proper image of the key predator of the forest ecosystem—the grey wolf.